Analisis Penerapan Serta Perbandingan Permasalahan Operasional Perusahaan pada PT. Gudang Garam Tbk Menjelang Pandemi - Fendy Cuandra; Shirley Feblicia; Tethannia Krishermawanti; Gusfandi Gusfandi; Daniel Daniel (Universitas Batanghari, 2023)
In implementing company operations, maximizing the performance of the company requires operational management to carry out its work as the most valuable and important part to be understood by the company. PT. Gudang Garam TBK as a company engaged in the manufacture of clove cigarettes, known as kretek cigarettes, is the object of this study. The research method used is to collect documentation, information and news relating to PT. TBK Salt Warehouse. The results of the research show that: (1) PT. Gudang Garam TBK continues to increase market share in this industry, there are many competitors, the decline in the economy and people's purchasing power, the pandemic, the increase in excise tax are all challenges by the company; (2) During the pandemic, PT. Gudang Garam TBK continues to fulfill its promise to ensure that customers have access to a variety of Gudang Garam goods that are of high quality and a consistent level of freshness, easy to obtain, and meet customer needs; (3) The difference is felt in the operations of PT. Gudang Garam TBK before the pandemic employees worked in factories without anyone WFH so that their operations could be controlled properly; (4) In quality control it is known that PT. Gudang Garam TBK will continue to carry out and carry out its objectives in following the wishes of consumers so that they can be interested and buy the company's products which will also increase sales.